Productivity, profitability and energy use efficiency of wheat-maize cropping under different tillage systems - Jaffar Iqbal; Tasneem Khaliq; Ashfaq Ahmad; Khuram Shehzad Khan; Md Ali Haider; Muhammad Moaaz Ali; Naeem Ahmad; Muhammad Ishaq Asif Rehmani (Farming System)
The energy consumption of intensive tillage practices is higher, decreasing soil and environment sustainability. Conservation agriculture practices i.e. reduced or no-tillage could be suitable options to conserve energy and environment and increase profitability. However, previous studies evaluated the energy consumption, productivity and profitability in two or three tillage systems, a comprehensive assessment of multiple tillage systems is needed. Therefore, six tillage i) conventional (CT), ii) conventional with bed (CTB), iii) reduced (RT), iv) reduced with bed (RTB), v) zero (ZT), and vi) zero with bed (ZTB) were practiced to evaluate the energy consumption, productivity of wheat-maize and their economic returns. The results showed that CT, RTB, RT, ZTB, and ZT reduced 21% and 13%, 81% and 93%, 36% and 56%, 169% and 263%, and 81% and 152% energy consumption than CTB in wheat and maize, respectively. Considering mean productivity, CT and CTB increased by almost wheat (953.43 ​kg ​ha−1) and maize (466.66 ​kg ​ha−1) yields. However, ZT, and RT had higher EP (energy productivity, 32%) and EUE (energy use efficiency, 30%) in wheat, 14% EP and 10% EUE as compared to CTB in maize. The lower EP and EUE in maize were mainly due to higher inputs/energy consumption in comparison to wheat. The input cost of CT, and CTB was higher in wheat than in other tillage practices, but the wheat yield was statistically similar in CT, CTB, RT, and RTB in both years. The RT had a higher benefit-cost ratio (BCR) in wheat (1.52) and maize (0.74) than intensive CT practice (1.44 (wheat), 0.61 (maize)). In wheat, EUE and EP were significantly higher under RT and ZT treatments, however, both were significantly reduced under bed plantation, contrarily no specific trends were observed in maize. In conclusion, RT could be used for wheat cultivation that consumed lower energy inputs and produced higher EUE, EP, and statistically equal grain yield as compared to CT. However, this practice might not be useful for maize cultivation and needs further evaluation.